Análise de fatores determinantes na viabilidade econômica de investimentos em energia solar e eólica - Azevêdo, Rômulo de Oliveira (2020)
The growing demand for electricity and the environmental and energy crisis in the world have highlighted studies on alternative sources of energy, which can supply this demand and mitigate the damage caused to the environment. Renewable energies, such as wind and solar energy, are the main sources of alternative energy sought in the world because they are considered clean and abundant sources of energy in almost the entire planet. Although it is necessary to install such energy sources, it is essential to assess the factors that impact on the economic viability of the projects, in order to facilitate and encourage investors in the installation of these renewable energy sources. Therefore, the objective of this research is to present a systematic analytical framework, to identify and analyze the main factors that impact on the financial feasibility study of a project for the installation of wind and solar plants. For that, a Systematic Literature Review (RSL) was carried out through the Web of Science (WoS), in order to analyze the main studies related to the theme and to identify the main factors that can financially affect the investment in such energy sources. The RSL processes basically involved three stages: the entry stage; the processing step; and the exit step. Two research studies were carried out: the first for studies on the economic viability of wind energy; and the second for studies on the economic viability of solar energy. The factors found in the two RSL processes were classified into five categories: (i) location factors; (ii) economic factors; (iii) political factors; (iv) climatic and environmental factors; and (v) technical factors. In the case of solar energy, 29 influencing factors have been identified. Among them, we highlight the initial investment costs, energy generation, operation and maintenance, solar radiation, efficiency, energy tariff, electricity consumption and interest and taxes. In the case of wind energy, 23 parameters were identified as impact factors, with installed power being the most prominent factor, present in all studies of the final sample, followed by investment cost, wind speed, time of useful life and the cost of operation and maintenance. The results can help policy makers, investors, researchers and other stakeholders to identify the main factors being examined in the literature and to assess which ones should be considered in their study to ensure sustainable development of energy generation through these sources.